The Sanitation Cityscape – Toward a Conceptual Framework for Integrated and Citywide Urban Sanitation - Scott, Pippa; Cotton, Andrew P. (Frontiers in Environmental Science, 2020)
In the last decade, the sanitation service chain model has become the de facto framework for much research and development in urban non-networked sanitation. People, their priorities and urban ways of living, as well as the conditions that underpin sustainable services, are too often overlooked in current conceptualizations of urban sanitation service delivery. This paper suggests that, as the sector moves toward a new paradigm of Citywide Inclusive Urban Sanitation, it is timely to revisit the conceptual framing of urban sanitation. The Sanitation Cityscape is a conceptual framework for citywide urban sanitation. It identifies the key factors of urban sanitation and locates those within a framework using three conceptual environments: The Living Environment, the Service Delivery Environment, and the Enabling Environment. Using a proposed set of 16 indicators and locating existing tools (for example, the Living Conditions Diamond, the fecal flow diagram, and the Citywide Service Delivery Assessment), the framework looks beyond the linear framing of sanitation services to gain a better understanding of the surrounding context and externalities. For the researcher and practitioner alike, we suggest that the Sanitation Cityscape can provide a coherent “frame” to locate the components of the urban sanitation puzzle predictably and systematically. It lends itself to rapid diagnostic analysis and more appropriate targeting of appropriate sanitation interventions. The paper includes insights from application of the Sanitation Cityscape framework including moving toward an outcome-based sanitation service delivery model, efficiencies in data collection, creating area typologies to align sanitation responses, setting enabling environment analyses boundaries purposefully and intentionally, and identifying key interfaces as potential intervention points or system levers. We hope that the Sanitation Cityscape might provide a foundation for greater consistency and a common vocabulary around the fundamental concepts and indicators relevant to urban sanitation.